Philosophical Perspectives on Memory and Imagination - Berninger, Anja; Vendrell Ferran, Ingrid (Routledge Studies in Contemporary Philosophy, 2023)
This book explores the structure and function of memory and imagination, as well as the relation and interaction between the two states. It is the first book to offer an integrative approach to these two emerging areas of philosophical research. The essays in this volume deal with a variety of forms of imagining and remembering. The contributors come from a range of methodological backgrounds: empirically minded philosophers, analytic philosophers engaging mainly in conceptual analysis, and philosophers informed by the phenomenological tradition. Part 1 consists of novel contributions to ontological issues regarding the nature of memory and imagination and their respective structural features. Part 2 focuses on questions of justification and perspective regarding both states. The chapters in Part 3 discuss issues regarding memory and imagination as skills or abilities. Finally, Part 4 focuses on the relation between memory, imagination, and emotion. Philosophical Perspectives on Memory and Imagination will be of interest to scholars and advanced students working in philosophy of memory, philosophy of imagination, philosophy of mind, and epistemology.